2020
DOI: 10.1016/j.watres.2020.115891
|View full text |Cite
|
Sign up to set email alerts
|

Two years of post-wildfire impacts on dissolved organic matter, nitrogen, and precursors of disinfection by-products in California stream waters

Abstract: We investigated the effects of two California wildfires (Rocky and Wragg Fires, 2015) compared to an unburned reference watershed on water quality, dissolved organic matter (DOM), and precursors of disinfection by-products (DBPs) for two years' post-fire. The two burned watersheds both experienced wildfires but differed in the proportion of burned watershed areas. Burned watersheds showed rapid water quality degradation from elevated levels of turbidity, color, and suspended solids, with greater degradation in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
57
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(60 citation statements)
references
References 71 publications
2
57
1
Order By: Relevance
“…While the effects of wildfire on turbidity in ocean ecosystems have not been previously documented, investigations on the effects of wildfire on turbidity in stream ecosystems have associated heightened turbidity levels to burn severity 29 and precipitation events 23 , 25 28 , 30 , 31 . In addition, when compared to plumes from urban stormwater runoff in the Santa Monica Bay 50 , 51 , plumes from burned area surface runoff were greater.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While the effects of wildfire on turbidity in ocean ecosystems have not been previously documented, investigations on the effects of wildfire on turbidity in stream ecosystems have associated heightened turbidity levels to burn severity 29 and precipitation events 23 , 25 28 , 30 , 31 . In addition, when compared to plumes from urban stormwater runoff in the Santa Monica Bay 50 , 51 , plumes from burned area surface runoff were greater.…”
Section: Discussionmentioning
confidence: 99%
“…Due to slow watershed recovery, post-fire sediment yields can remain elevated for 3 months to 10 years 19 . Accordingly, studies have reported short-term 23 , 24 , 26 , 28 , 30 and long-term 25 , 27 , 29 , 31 turbidity increases in streams post-fire. The current study did observe short-term increases in turbidity, within 3 months of the Woolsey Fire.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the loss of human life and property, wildfires can degrade water quality, thus threatening the supply of safe drinking water (Hohner et al, 2016;Uzun et al, 2020;Writer et al, 2014). In 2018, the 5-and 10-year average for acres burned in the United States was exceeded, spurring concern and skepticism over the future of wildfire's anthropogenic and ecological influence (Doerr & Santín, 2016;National Interagency Fire Center, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…However, oftentimes, it is difficult to separate the effects of a wildfire from routine hydrologic events (Mast et al, 2016). Similar to DOC, post fire dissolved organic nitrogen (DON) trends are also largely variable, with some studies reporting little to no change and others observing increased DON concentrations in surface waters from burned catchments (Bladon et al, 2008;Santos et al, 2019;Uzun et al, 2020). Detritus is mineralized as a result of wildfire heating, effectively lowering the elemental carbon and nitrogen content available for transport.…”
Section: Introductionmentioning
confidence: 99%